KONSTRUKSI LELAKI DALAM CHICKLIT “THE HOPELESS ROMANTIC’S HANDBOOK” DAN “CINTAPUCINNO” - Subekti, Mega; Gumilar, Trisna (SUAR BETANG, 2017)
In popular literature, chicklit is one of the genres that focuses on the  women's issues. For some scholars chicklit has a simple formula.   In cultural studies, chicklit enriches  various discourses especially the discourse of feminism.In this paper, analyzed about the construction of men in  "The Hopeless Romantic's Handbook" by Gemma Townley's (2008) and "Cintapucinno" by Icha Rahmanti (2007). The construction of identity (men/women) is an important object in study of feminist discourse. The results of the study show that heroines construct ideal men’s standards. In gender discourse, the construction of men’s physical appearance and their symbol are considered as an activity or value equivalent as well as men constructs the identity and stereotypes of women through their bodies